PERTANGGUNGJAWABAN PIDANA PELANGGARAN IZIN TINGGAL YANG DILAKUKAN WNA STUDI KANTOR IMIGRASI KELAS II TPI TANJUNGBALAI - Erwin Syahputra; Rizka Handayani; Nurma Anggita Putri; Pelangi Pelangi; Dimas Dimas; Putri Putri6,; Della Della; Nauval Nauval; Doly Doly; Winda Winda; Fatika Fatika; Fahri Azmi; Herman Herman; Agave Agave; Akbar Akbar; Adelia Adelia (Nusantara Hasana Journal, 2022)
Foreign citizens who wish to enter and reside in the Republic of Indonesia are regulated in Law No. 6 of 2011 concerning Immigration regarding entry and exit of the NKRI area, NKRI expedition documents, visas, entry characteristics, and requesting to reside, overseeing the immigration system, immigration system actions , as well as investigations. In this legal research using empirical legal research methods and conducting studies at the Immigration Office Class II TPI Tanjungbalai. In this legal research, primary legal materials are used, namely: Interviews. Secondary legal materials, namely: law books. Tertiary legal materials, namely: non-legal books. The process of carrying out enforcement duties for foreigners who enter the State of Indonesia, especially the Tanjungbalai City area and its surroundings who are proven to have misused travel documents if found by the officers of the Tanjungbalai TPI Class Immigration Office, then the actions/efforts taken by the officers are to carry out surveillance first. and the presence of foreigners who are in the jurisdiction of the Tanjungbalai Immigration Office Class TPI can directly arrest, interrogate and investigate and if or it is reasonably suspected that the foreigner is carrying out activities that are not in accordance with his residence permit, the foreign national will be detained and investigated for further submission. to the Public Prosecutor at the Tanjungbalai Asahan District Prosecutor's Office to be carried out p21. barriers to cracking down on misuse of travel documents by foreigners, which include the following: Language translators who are not in the working area in Tanjungbalai City in dealing with foreigners who enter Indonesian territory, especially Tanjungbalai City, the foreigner's representative does not exist in Indonesia, Limited budget for coordinate with related agencies; and Lack of Human Resources (HR) who have a PPNS Card (Civil Servant Investigator).